Black carrot (Daucus carota L.), dietary and health promoting perspectives of its polyphenols: A review. (August 2017) - Akhtar, Saeed; Rauf, Abdur; Imran, Muhammad; Qamar, Muhammad; Riaz, Muhammad; Mubarak, Mohammad S.
Abstract: Background: The last few decades have witnessed a paradigm shift from the consumption of synthetic and processed foods towards natural food products because of their excellent health features. These trends are not only reshaping the approach to defend multiple ailments but also have opened avenues for scientific exploration to cure various physiological disorders. Scope and approach: The present review primarily aims at spotlighting the presence of potential phytochemicals in black carrots ( Daucus Carota L.) and their significant role in several major metabolic syndromes, such as cancer, cardiovascular diseases (CVD), diabetes mellitus, obesity, and oxidative stress-induced other malignancies. In addition, the current comprehensive review focuses on the chemistry and pharmacokinetics of black carrot polyphenols and proclaims black carrot anthocyanins as the major biological fractions to offer disease prevention and to some extent curative properties. Key findings and conclusions: In addition to its remarkable anthocyanins profile, black carrots are good source of a wide array of flavonoids evidently reported to avert a myriad of degenerative diseases. Health and therapeutic characteristics of these bioactive compounds call for further explorative studies and research endeavors to exploit this vegetable for prevention and cure of many diseases. Highlights: Black carrot as an important dietary supplement. Phytochemicals in black carrot. Role of black carrot's polyphenols as therapeutic agents. Anthocyanins can be potential drugs against a number of diseases, including cancer. This work represents an updated review on black carrots, its phytochemicals, and diseases prevention.